PENGARUH KUALITAS PELAYANAN DAN SUASANA LOKASI TERHADAP KEPUASAN PEMBELI PADA DEPOT ASIH DI KABUPATEN TULUNGAGUNG JAWA TIMUR - Sindu Anstasari Mekaring Arum; Sunanik Sunanik (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2021)
This study aims to determine the satisfaction of buyers who are influenced by the quality of service and the atmosphere of the location at the Asih Depot in Tulungagung, East Java. This research is a quantitative research. A total of 96 respondents in this study were sampled from some buyers of the Asih Depot. The population in this study are Depot Asih buyers. The sampling technique in this study uses the method of accidental sampling. The research variables are Service Quality (X1), Location Atmosphere (X2), and Buyer Satisfaction (Y). Data collection techniques using observation and questionnaire methods (questionnaire) to obtain data on Service Quality, Location Atmosphere and Buyer Satisfaction. Data analysis techniques using the SPSS version 21 for windows.The results of data analysis in this study indicate simultaneously F_count (15.315)> F_tabel (3.09) and a significant level of 0.000 ˂ 0.05, so that it can be concluded that there is a significant influence on Service Quality and Location Atmosphere Against Buyer Satisfaction at the Asset Depot in Tulungagung Regency, East Java.